In-line digital holography for dynamic metrology of MEMS - Singh, Vijay Raj (2011)
In-line digital holography helps to relax the spatial resolution requirement on charge-coupled device sensors for digital recording of holograms and to utilize the full sensing area for image reconstruction which provides larger field of view and better imaging resolution. In this letter, a lensless in-line digital holographic microscopy is presented for dynamic metrology of micro-electro-mechanical systems devices. The methodologies of interferometry and time-averaged in-line digital holography are presented for dynamic measurements, which are also useful for simultaneous suppression of in-line waves from real image wave. The experimental results are presented for dynamic thermal characterization of microheater and vibration analysis of cantilevers.